Estudio de factibilidad para la creación de una empresa comercializadora de jugo de naranja para el desayuno escolar de los estudiantes de educación básica en el cantón Quinsaloma, periodo 2014 – 2015 - Franco Bone, Willian Walberto (2015)
Quinsaloma city has experienced in the last year a considerable growth in the student population in basic level, and enjoys a huge orange production, the raw material to meet project objectives. The current "FEASIBILITY STUDY FOR THE ESTABLISHMENT OF A DISTRIBUTOR OF ORANGE JUICE COMPANY FOR SCHOOL STUDENTS IN BASIC EDUCATION BREAKFAST Quinsaloma Canton, PERIOD 2014 - 2015" it has been designed according to the technical circumstances and needs of the product to deliver. Quinsaloma is a purely agricultural county was dedicated to the cultivation and production of orange, among others. The development of a natural fruit juice is an alternative that contributes to the development of our community, economic, social, cultural and personal level as far as health is concerned, orange extract, is a drink rich in vitamin "C "why we recommend regular consumption of this fruit, to bring considerable benefits in the nutrition of adults and especially children. Through our research project is to determine what may have mounting feasibility of an industrial plant, marketer of orange juice for breakfast school students in basic education in the Quinsaloma Canton ?, and answer that question. The survey, interview and direct observation both primary and secondary sources: for which the deductive, inductive and analytical methods for the collection of information and the use of investigative techniques as are used. Then through the market survey, the unmet demand for 3506 students by 2015 in relation to food consumption provided by the Ecuadorian State to elementary school students of the town was determined, which is why the including our drink would be an alternative variation in the stock of nutritional products that deliver the Ministry of Education to students, being a different option in taste, presentation and also for their contribution of nutrients that undoubtedly contribute to the welfare of children and those who consume. Also the location of the plant is established, where the optimal place for the location of the plant is in the Quinsaloma Canton, same to be located on the outskirts of the city in the Allotment "The Morelia" in addition to determining the production process, product features based on student preferences will a drink abstract orange juice with natural sweetener in presentations orange, and what furniture and fixtures necessary for the operating process will be the plant. Through economic and financial evaluation of investment feasibility of our proposal, which, through financial study provides an NPV of $ 380.10 and an IRR of 13.39% being within the margins of profitability and stability is demonstrated liquidity that enable economic development with the cash flow required for operation and obtaining the expected benefits.